ANALYSIS ON THE CAUSES OF NONPERFORMING LOAN AT BANK XYZ MANADO - Saliem, Stenly C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Bank works to bridge both people who have excess funds with the people who need funds. In practice not all of the funds raised from the public may be channeled properly to the public and usually have problems in terms of loan repayments to the bank and almost all banks in Indonesia experiencing nonperforming loan. This study is to know the factors that cause nonperforming loan at Bank XYZ Manado using qualitative method. The samples of respondent are 6 peoples who are the credit analyst at Bank XYZ main office. The result shows that there are 3 factors that cause nonperforming loan which are bank factors, debtor factor and external factors. The problem from bank factor is their incapability of human resources; the debtor factors are bad management and fraud; while for the external factors are disasters and government policy. The recommendation for company are to create a proper training program and improve the standard of credit analyst. To increase the awareness and motivate the credit analyst in granting a loan, bank can implement the reward and punishment system. Keywords: nonperforming loan, bank factors, debtor factors, external factors